2018
DOI: 10.1039/c7sc04665k
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for the structure–energy–property landscapes of molecular crystals

Abstract: Polymorphism is common in molecular crystals, whose energy landscapes usually contain many structures with similar stability, but very different physical–chemical properties. Machine-learning techniques can accelerate the evaluation of energy and properties by side-stepping accurate but demanding electronic-structure calculations, and provide a data-driven classification of the most important molecular packing motifs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
217
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(229 citation statements)
references
References 81 publications
6
217
1
Order By: Relevance
“…Due to the various competitive noncovalent intermolecular interactions, computational prediction is necessary for the design of molecular crystals. Musil et al reported a novel ML framework for high‐accuracy property prediction of polymorphs. With Gaussian Process Regression (GPR) built on the SOAP (Smooth Over of Atomic Positions)‐REMatch kernel, the model can be applied to predict relative energetics of crystal materials and the transfer integrals that are calculated to predict charge mobility of molecular crystals, and the promise of high accuracy can be satisfied which is demonstrated by cross‐validated predictions.…”
Section: Achievements Of ML In Energy Storage and Conversion Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the various competitive noncovalent intermolecular interactions, computational prediction is necessary for the design of molecular crystals. Musil et al reported a novel ML framework for high‐accuracy property prediction of polymorphs. With Gaussian Process Regression (GPR) built on the SOAP (Smooth Over of Atomic Positions)‐REMatch kernel, the model can be applied to predict relative energetics of crystal materials and the transfer integrals that are calculated to predict charge mobility of molecular crystals, and the promise of high accuracy can be satisfied which is demonstrated by cross‐validated predictions.…”
Section: Achievements Of ML In Energy Storage and Conversion Materialsmentioning
confidence: 99%
“…Moreover, the accuracy of the model was effectively improved by a novel material property, which is called excess Born effective charge. Another ML classifier reported by Musil can help researchers to understand the packing and the self‐assembly mechanism of molecular materials. Such automatic classification tool shows superiority compared with the heuristic classifications.…”
Section: Achievements Of ML In Energy Storage and Conversion Materialsmentioning
confidence: 99%
“…To our knowledge, this is the largest set of molecules that has been subjected to CSP and prop- Figure 1: The known (1) and hypothetical (2-28) molecules studied. Symmetrical (C 2v ) isomers (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) are colored in orange, to contrast with the asymmetric (C s ) isomers (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%
“…This density-based representation can be adapted to incorporate correlations between atoms to any order. It has been applied successfully to a vast number of machine learning investigations for physical properties of atomic structures [26][27][28]. After summarizing the derivation and efficient implementation of an extension to SOAP, called λ-SOAP, which is particularly well-suited to the learning of tensorial properties, we present a few examples to demonstrate its effectiveness for this task.…”
Section: Introductionmentioning
confidence: 99%